Penerapan Program CBP Rupiah Pada Siswa SMAN 2 Medan Melalui Studi Ekskursi - Amanda Ramadhanty; Rahma Ida Siregar (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The Love, Pride, and Understanding Rupiah (CBP) Program, initiated by Bank Indonesia, aims to enhance financial literacy and public awareness, particularly among students, regarding the importance of the Rupiah as a symbol of national sovereignty and a legal means of payment. This study explores the implementation of the CBP program at SMA Negeri 2 Medan through an educational excursion to the Representative Office of Bank Indonesia in North Sumatra Province. Using a qualitative method, the research involved Grade X students participating in lessons about financial institutions. The program focuses on three main aspects: recognizing the design and characteristics of the Rupiah, safeguarding against counterfeit currency crimes, and maintaining the Rupiah in good condition. The study's findings show that the activity successfully improved students' understanding of the Rupiah, particularly in terms of its authenticity, role in the economy, and fostering pride and love for Indonesia's currency. This study also highlights the importance of early financial literacy education to encourage wise financial behavior among students.